Health staff perceptions of patient safety and associated factors in hospitals in Vietnam - Nguyen Thi Hoai Thu; Bui Thi My Anh; Nguyen Thi Thu Ha; Doan Ngoc Thuy Tien; Pham Huong Giang; Tran Thi Nga; Nguyen Hoang Nam; Phung Thanh Hung (Frontiers Media S.A., 2023)
IntroductionPatient safety is a global challenge of preventing and mitigating medical errors which might harm patients during their course of treatment and care. This study was employed to contribute to the existing literature aimed to assess patient safety culture among health staff and to determine predictors of health staff perceptions of patient safety in hospitals in Vietnam.MethodsA cross-sectional study was conducted in three hospitals of Vietnam with a total of 763 participants. This study used the Hospital Patient Safety Scale developed by the American Health and Quality Research Organization.ResultsIn general, 8 of 12 patient safety dimensions in two hospital; and 10 of 12 dimensions in a third hospital had average scores of 60% and above positive responses. The communication openness and organizational learning dimensions were found to be significant different when comparing hospitals. Regarding sample characteristics, department (subclinical department) and health staff positions (nurses/technicians, pharmacists) were significant predictors in the total model including three hospitals (R2 = 0.07).ConclusionThis study reported that communication openness and organization learning are two aspects that need to be improved they are strongly related to patient safety culture and to knowledge exchange among health staff. It has been suggested that hospitals should deliver patient safety training courses and establish a supportive learning environment to improve these challenges.